Students’ Perception of Learning English as Specific Purpose through Collaborative Learning of Classroom Implementation - Hastuti, Hilda; Alfilail, Nur; Syarifaturrahman, Wahyu Kamil (Humanitatis : Journal of Language and Literature, 2024)
The collaborative learning model requires students to play an active role in learning English, where students can share ideas, solve problems, think critically by collaborating to achieve learning goals. The aim of this research is to determine the perceptions of class E undergraduate management study program students regarding the implementation of the collaborative learning model in English language learning. The method used in this research is qualitative with a qualitative descriptive approach. The population in this study were all 40 class E students and sampling in this study was used non-random sampling, purposive sampling technique. 37 students were taken as sample. The instrument used was questionnaire which was distributed on google form. The 37 total respondents who filled out the questionnaire, only 28 respondents. However, the 28 respondents represent students' perceptions of implementing collaborative learning in English language learning. The research results show that students positively perceive implementing the collaborative model in English language learning. The implication of this study is collaborative learning might be implemented for teachers or lecturers in the teaching and learning process with other subjects.